Anaesthesia for renal transplantation. Issue 10 (October 2018) - Robertson, Emily; Logan, Neil; Pace, Nick
Abstract: This article describes the assessment of the patient for renal transplantation, the perioperative management and the aims in the post-operative period. These patients present a unique set of challenges to the anaesthetist, who has a crucial role in the immediate success of the transplanted organ.